(3Daj CNHGQ GdNdaGAs - (3CHh eQhGf YHO Gdedc Hf GdcQOHhS, GdJhRQj GdJhfSjs
(3ChdgG (B:s
(3MOK YeQh Hf GdYGU QMeg Gddg bGd (B: (3deG EfUQafG eY GdCMRGH ai GdNfOb LeYJ QLGdkG ef bQjT cGfhG jQhf QCji hjSeYhf efi , abdJ dge JYdehG hGddg Efi CQi CeQ eMeO jYdh s
(3BNQgG (B:s
(3ef YfhGf (B: (3hbYI GdjQehc Ydi fMh eG McGg CUMGH cJH aJhM GdTGe , bhdg (B: (3bGd (B: (3aCcH YeQ WhjdkG hai jOg YUGdg , hgh hGVY LHgJg YdjgG , Ke QaY QCSg JeGe GdNHQ Yf hbYI GdjQehc ced GdKdK GdKGfi ef cJGH GdEcJaGA HMeO Gddg s
(3GdKdK GdKGfis
(3ai GdeYgO fSNI CNQi HQbe (B900 (3JGQjNs
(3cJHJ Hbde eVHhWs
(3HBNQgG Jedc HGdTQGA YGe (B1216 (3g` s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs